Kosovo : Healing Land for the Future - World Bank (World Bank, Washington, DC, 2019)
This report provides a recommended program for contaminated site management over a relatively long (20-year) time horizon. This program will help Kosovo to prevent potentially significant unforeseen consequences in several economic areas, including real estate markets and public budgets, and to avoid the pressure to accept legislation that is not optimal for the country’s social and environmental needs. The program will also assist Kosovo’s compliance directly and indirectly with existing and emerging EU legislation and strategies as a part of its European Union (EU) accession candidacy. This report focuses on the legacy from point sources (contaminated sites). The recommended program is a well-defined and investable program, strongly oriented toward capacity building and a learning-by-doing approach for Kosovar stakeholders and practitioners. The program reflects good practice in management, policy, and regulation in other European countries (Nathanail et al. 2013). Moreover, it builds upon the World Bank advisory report on Developing a Program for Contaminated Site Management in Low- and Middle-Income Countries (Kovalick and Montgomery 2014). The intended audience of this report is twofold. The technical assessment sections (chapters two, three and Annex one, two) target practitioners and stakeholders in contaminated site management in Kosovo (including agencies, regulators, planners, local authorities, site owners and operators, academics, consultants, and contractors). The Executive Summary and the guiding principles and recommended program for contaminated site management (Chapter four) would also be of interest to policy makers.